High Voltage Engineering - Rizk, Farouk A.M; Trinh, Giao N. (New York : CRC Press, 2014)
"This self-contained book supplies background information and gives an up-to-date understanding of high-voltage engineering. It covers the physical phenomena active in insulation systems, the various factors affecting insulation performance, and the actual means of evaluating the insulation performance and their application in the establishment of technical specifications. In addition, the book discusses the design, selection, and testing of high-voltage power equipment and their maintenance practices. The emphasis is on how to deal with practical situations that may be encountered in operating high-voltage power equipment"--
Keywords: Electric power distribution -- High tension; High voltages; Electrical